Reinforcing the Perception of Climate Education and Educational Climate among Academicians and Practitioners in Banten Province through Collaborative Learning - Clara Shabrina Parameswary; Sandi Danar Cynthia Sari; Tresna Galih Sukma Suryana; Devi Ayu Nur’aini; Dinar Nirmalasari; Dudung Abdurrahman; Annisa Novianti Taufik; Sindanita Yulianty; Dewi Murni; Tri Retno Wulan (Smart Society, 2026)
Climate education (literacy and awareness of climate) and educational climate (pedagogical atmosphere) are two similar phrases that their implementation are vitals in education.  The reinforcement of these two aspects were sometimes less highlighted in a scientific forum. This event aims to bring a refreshment within higher education, teachers, and stakeholders in Banten Province of these two themes. The event was organized by lecturers of the science clusters (comprising those from math, physics, chemistry, natural science, and biology) from FKIP Untirta in collaboration with Association of Indonesian Teacher in Serang City (IGI Kota Serang). The event began with an interactive talk show followed by active sharing session involving participants that were grouped according to the subject or field of study and enriched with demonstration of learning media and instruments to support the implementation of climate education and school climate practices. Research was carried out to to examine perceived usefulness and knowledge gain of respondents towards the event. Data was collected from the respondents by filling out an online survey and qualitative analysis was performed. The interpretation of the data was explained descriptively. More than half of the participants had little understanding related to the topic prior to the event but found that participants perceived an increase in knowledge and confidence level of climate education and educational climate to implement and integrate the knowledge at school. To conclude, most participants perceived the event as successful in leveraging ideas of climate education and implementing educational climate at school.